2018
DOI: 10.5194/amt-11-6107-2018
|View full text |Cite
|
Sign up to set email alerts
|

The CALIPSO version 4 automated aerosol classification and lidar ratio selection algorithm

Abstract: Abstract. The Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) version 4.10 (V4) level 2 aerosol data products, released in November 2016, include substantial improvements to the aerosol subtyping and lidar ratio selection algorithms. These improvements are described along with resulting changes in aerosol optical depth (AOD). The most fundamental change in the V4 level 2 aerosol products is a new algorithm to identify aerosol subtypes in the stratosphere. Four aerosol subtypes are introduced for stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
316
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 414 publications
(376 citation statements)
references
References 104 publications
14
316
0
Order By: Relevance
“…The V4 probability density functions reflect extensive calibration updates in level 1 data to more accurately differentiate clouds and aerosols. These updates have improved previous misclassifications of lofted dust and smoke, as well as stratospheric aerosol layers (Kim et al, ). All aerosol layers detected between the surface and 30‐km altitude are classified by type.…”
Section: Methodsologymentioning
confidence: 95%
See 1 more Smart Citation
“…The V4 probability density functions reflect extensive calibration updates in level 1 data to more accurately differentiate clouds and aerosols. These updates have improved previous misclassifications of lofted dust and smoke, as well as stratospheric aerosol layers (Kim et al, ). All aerosol layers detected between the surface and 30‐km altitude are classified by type.…”
Section: Methodsologymentioning
confidence: 95%
“…To better understand the impacts of anthropogenic aerosols, we quantify the contributions to DRE of individual aerosol types. This study will present results for several aerosol types, as identified using the CALIPSO version 4.1 (V4) aerosol classification (Kim et al, 2018).…”
Section: Methodsologymentioning
confidence: 99%
“…Data with PDR values in between the thresholds of dust and nondust are considered as a mixture, and a fraction of dust in such mixture is derived from the definition of PDR (Yu et al, , Yu, Chin, Bian, et al, ). Dust extinction is then calculated by multiplying the so‐obtained dust backscatter coefficient by the characteristic dust lidar ratio of 44 sr, consistent with the number used in the CALIOP V4 product (Kim et al, ). Finally, CALIOP DOD is calculated by integrating the dust extinction profile in the vertical.…”
Section: Data and Approachesmentioning
confidence: 99%
“…Two data sets were used in this study employing the preceding instruments. The merged CloudSat CALIPSO 2B CLDCLASS LiDAR R04 product (hereafter combined CloudSat/CALIPSO) combined with the European Centre for Medium‐range Weather Forecasts Auxiliary (ECMWF‐AUX) product (Partain, ; Sassen et al, ; Wang et al, ) and the merged aerosol and cloud CALIPSO 5 km (level 2, v4.1) layer product (Kim et al, ; Winker, ).…”
Section: Methodsmentioning
confidence: 99%
“…We should mention here that data from CALIPSO version 3 have been used to retrieve the combined CloudSat/CALIPSO data set (R04). This older version of CALIPSO algorithms have been improved since and evaluated, to some extent, against the newer one (v4.1; Kar et al, ; Kim et al, ). A notable difference from v3 is that all aerosol subtypes are allowed over polar region and the aerosol classification algorithm no longer uses snow, ice, and tundra as decision points.…”
Section: Methodsmentioning
confidence: 99%